A Fluorescent Sensor for Highly Selective Detection of Nitroaromatic Explosives Based on a 2D, Extremely Stable, Metal–Organic Framework. Issue 13 (27th February 2014) - Zhang, Shu‐Ran; Du, Dong‐Ying; Qin, Jun‐Sheng; Bao, Shao‐Juan; Li, Shun‐Li; He, Wen‐Wen; Lan, Ya‐Qian; Shen, Ping; Su, Zhong‐Min
Abstract A 2D, extremely stable, metal–organic framework (MOF), NENU‐503, was successfully constructed. It displays highly selective and recyclable properties in detection of nitroaromatic explosives as a fluorescent sensor. This is the first MOF that can distinguish between nitroaromatic molecules with different numbers of NO2 groups.